2019
DOI: 10.1186/s13071-019-3636-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and gut ultrastructure of Anisakis pegreffii isolated from stranded cetaceans in the Adriatic Sea

Abstract: Background Inferring the microbiota diversity of helminths enables depiction of evolutionarily established ecological and pathological traits that characterize a particular parasite-host interaction. In turn, these traits could provide valuable information for the development of parasitosis control and mitigation strategy. The parasite Anisakis pegreffii (Nematoda: Anisakidae) realizes the final stage of its life-cycle within gastric chambers of aquatic mammals, causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Interestingly, all anisakid nematodes collected in this study were classified as L4 larvae of A. pegreffii. We suggest that the Clymene dolphin may acts as a definitive host for this species, because A. pegreffii mature in the stomach of other dolphin species (e.g., Mladineo et al, 2019;Pons-Bordas et al, 2020). We believe that these nematodes were likely recruited by the Clymene dolphin in Patagonia.…”
Section: Parasite Diversity and Life-cyclementioning
confidence: 85%
“…Interestingly, all anisakid nematodes collected in this study were classified as L4 larvae of A. pegreffii. We suggest that the Clymene dolphin may acts as a definitive host for this species, because A. pegreffii mature in the stomach of other dolphin species (e.g., Mladineo et al, 2019;Pons-Bordas et al, 2020). We believe that these nematodes were likely recruited by the Clymene dolphin in Patagonia.…”
Section: Parasite Diversity and Life-cyclementioning
confidence: 85%
“…Considering that C. oestroides lives in buccal cavity of its host with a sufficient oxygen supply where it can rely on oxidative metabolism, lipid storage over glycogen storage is more feasible, compared to some endoparasites, e.g. nematodes, in which glycogen storage is favored due to hypoxic environment of host's body cavities in which they reside [32]. The presence of numerous vesicles around lipid droplets with likely proteinaceous content remains puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…Although Anisakis sp. L3 are non-active feeding stages, a recent study demonstrated the presence of several vesicles in the L3 intestinal lumen, potentially originating from passive intake during migration through the tissues of their paratenic hosts [41]. It is likely that a part of these “ingesta” in the form of nutrients finally reaches the EC and passes by endocytosis, as the cell is already active at this larval stage and requires energy for ES production.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, anaerobic glycolysis that mostly occurs in the cytosol in an oxygen-independent metabolic pathway converts glucose into pyruvate, storing the energy in form of ATP and NADH. Both somatic muscle and enterocytes of L3 have been observed rich in glycogen [41], suggesting that glycolysis might be an important metabolic pathway at the larval stage, engaged also in functioning of the EC.…”
Section: Discussionmentioning
confidence: 99%